2013
DOI: 10.1038/modpathol.2012.226
|View full text |Cite
|
Sign up to set email alerts
|

FOXL2 molecular testing in ovarian neoplasms: diagnostic approach and procedural guidelines

Abstract: A single, recurrent somatic point mutation (402C-G) in FOXL2 has been described in almost all adult-type granulosa cell tumors but not other ovarian neoplasms. Histopathological features of adult-type granulosa cell tumors can be mimicked by a variety of other tumors, making diagnosis of adult-type granulosa cell tumor challenging. It has been suggested that molecular testing for FOXL2 mutation might be a useful tool in the diagnosis of adult-type granulosa cell tumors. The aim of this study was to demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 13 publications
2
63
0
1
Order By: Relevance
“…3). This data is in keeping with the 2013 study by Kommoss et al (29), which highlighted the utility of FOXL2 mutation testing in the original and relapsed tumor, in a single case of unclear or mistaken gynecological diagnosis (29). As a practical consequence, in cases of metastasis from unknown primary lesions, the positivity of the molecular analysis of FOXL2 could assist the pathologist in finding the correct diagnosis of GCT of the ovary, as shown by the present data.…”
Section: Discussionsupporting
confidence: 69%
“…3). This data is in keeping with the 2013 study by Kommoss et al (29), which highlighted the utility of FOXL2 mutation testing in the original and relapsed tumor, in a single case of unclear or mistaken gynecological diagnosis (29). As a practical consequence, in cases of metastasis from unknown primary lesions, the positivity of the molecular analysis of FOXL2 could assist the pathologist in finding the correct diagnosis of GCT of the ovary, as shown by the present data.…”
Section: Discussionsupporting
confidence: 69%
“…Recently, it has been shown that a high percentage of ovarian AGCTs harbor a somatic missence (gain of function) mutation in codon C134W (402C-G) of FOXL2 gene (26)(27)(28)(29)(30)(31)(32)(33). This involves a gene encoding a transcription factor known to be critical for granulosa cell development (26).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that molecular testing for FOXL2 mutation might be a useful tool in the diagnosis of adult-type granulosa cell tumors (Kommoss et al, 2013). It is classically known that preoperative serum level of CA125 is an important diagnostic and prognostic factor for the ovarian malignancies.…”
Section: Discussionmentioning
confidence: 99%